PERAN SERTA MASYARAKAT DALAM PERLINDUNGAN ANAK DARI TINDAK KEKERASAN (KAJIAN KENAKALAN ANAK) DI KOTA PEKANBARU TAHUN 2016 - Shinta Handayani Hidayat; Wan Asrida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
According to the Republic of Indonesia Law Number 35 of 2014 amendments to Law 23 of 2002 concerning Child Protection, Child Protection is all activities to guarantee and protect children and their rights so that they can live, grow, develop and participate optimally in accordance with human dignity and dignity, and get protection from violence and discrimination. The State, Government, Regional Government, Society, Family, and Parents or Guardians are obliged and responsible for the implementation of Child Protection. The number of delinquency cases that occurred in Pekanbaru City in 2016 hence the need for community participation. In accordance with Pekanbaru Mayor Regulation No. 36 of 2016 concerning Protection of Women and Children from Violence, to see the obligations and responsibilities of the community in the implementation of child protection, the researchers wanted to see the Community Participation in the Protection of Children from Violence (Child Delinquency Study) in Pekanbaru City in 2016.The purpose of this study was to determine the Participation of the Community in the Protection of Children from Violence (Child Delinquency Study) in Pekanbaru City in 2016. The theory used in this study was community participation. This research method uses descriptive type with a qualitative research approach. The location of the study was conducted in the city of Pekanbaru. The technique of collecting data is done by interviews, documentation and literature. While the data analysis technique is done in a qualitative descriptive way.The results of the study that the Participation of the Pekanbaru City Community in the Protection of Children from Violence (Child Delinquency Study) in Pekanbaru City in 2016 has not run optimally. Judging from the participation of the community organizations that have been carried out in the form of preventing acts of violence against women and children, providing information or reporting acts of violence against women and children to law enforcement or authorities and participating in the handling of victims of acts of violence.Keywords: Community Participation, Child Protection, Violence